2018
DOI: 10.18632/oncotarget.25197
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-deficient breast cancer shows early tumor recurrence and escape from dormancy

Abstract: Breast cancer patients who initially respond to cancer therapies often succumb to distant recurrence of the disease. It is not clear why people with the same type of breast cancer respond to treatments differently; some escape from dormancy and relapse earlier than others. In addition, some tumor clones respond to immunotherapy while others do not. We investigated how autophagy plays a role in accelerating or delaying recurrence of neu-overexpressing mouse mammary carcinoma (MMC) following adriamycin (ADR) tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 31 publications
2
45
0
Order By: Relevance
“…Complete medium was used to wash any remaining cells through the filter. Ki67 expression was determined as previously described by our group [ 20 , 21 ]. Cells were fixed with 70% ethanol and stained with anti-Ki67 for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Complete medium was used to wash any remaining cells through the filter. Ki67 expression was determined as previously described by our group [ 20 , 21 ]. Cells were fixed with 70% ethanol and stained with anti-Ki67 for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…However, they could be susceptible to immunotherapy if targeted before clinical recurrences [ 19 ]. Recently, we have reported that dormant tumor cells established by chemotherapy or radiation therapy became resistant to additional doses of these therapies but remained susceptible to immunotherapy [ 20 , 21 ]. Chemotherapy-induced immunogenic tumor dormancy maintained by the immune response has also been reported by others [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, results from a recent study showed the role of autophagy as an important regulator of metabolic tumor cell dormancy. That, the lack of autophagy, which is exploited as an important compensatory mechanism by tumor cells to provide their energy requirements, associates with an early breast cancer recurrence and escape from dormancy as demonstrated in neu-overexpressing mouse mammary carcinoma (MMC) [120].…”
Section: Metabolic Reprogrammingmentioning
confidence: 99%
“…Autophagy also promotes survival of DTC against chemotherapy-induced cell stress [126] . On the other side, in breast cancer the lack of autophagy is associated with early tumor recurrence and escape from dormancy [127] . It is important to note, that cellular dormancy is not just a feature of cancer cells but it also occurs in normal cells.…”
Section: Cellular Dormancy: Survival Of Non-proliferating Solitary Cellsmentioning
confidence: 99%